2001
DOI: 10.1097/00042737-200108000-00006
|View full text |Cite
|
Sign up to set email alerts
|

No clinical benefit of adding cisapride to pantoprazole for treatment of gastro-oesophageal reflux disease

Abstract: Addition of cisapride to pantoprazole provides no further benefit in the treatment of GORD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…Similar rates of adverse events (most of which were assessed as unrelated to the study drug) occurred in both treatment groups. Patient compliance with both study drugs was high (99.7% of the drug was taken), and in agreement with other reports 25 ,. 28 , 32 , 33 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar rates of adverse events (most of which were assessed as unrelated to the study drug) occurred in both treatment groups. Patient compliance with both study drugs was high (99.7% of the drug was taken), and in agreement with other reports 25 ,. 28 , 32 , 33 …”
Section: Discussionsupporting
confidence: 92%
“…Several studies have previously reported a marked improvement in the symptoms of GERD during 4 weeks of treatment with pantoprazole 24–26 . Similarly, with esomeprazole, symptom relief rates of 65–68% have been reported 27 .…”
Section: Discussionmentioning
confidence: 87%
“…The standard dose of a PPI plus cisapride (withdrawn from clinical use due to a cardiac adverse effect) is reported to have no significant additional benefit in curing or relieving symptoms of GERD [82]. A Japanese study showed the possibility of an additional benefit of mosapride with a PPI [76].…”
Section: Cq: Is An Acid Suppressant Effective For the Treatment Of Gerd?mentioning
confidence: 99%
“…In most cases proton pump inhibitors (PPIs) achieve the desired acid suppression when given once daily, they are widely accepted to be the best treatment option. It is generally accepted that PPIs are significantly superior to H 2 -receptor antagonists [5, 6, 7, 8], prokinetics [9]and placebo [for review see 10, 11, 12]. Further, it was previously shown that pantoprazole and omeprazole are highly efficacious in the treatment of mild [13]and moderate to severe GERD [14, 15].…”
Section: Introductionmentioning
confidence: 99%